REPRESENTASI KEKUASAAN TINDAK TUTUR DIREKTIF DALAM TALK SHOW INDONESIA LAWYERS CLUB DI TV ONE Representation of Power in Directive Speaking Actions on Indonesia Lawyer Club Talk Show TV One - Faidah, Nur; Karim, Ali; Harisah, Sitti (BAHASANTODEA, 2017)
This research intends to 1) describe representation form of power in directive speaking action on Indonesia Lawyer Club Talk Show TV One, 2) describe representation function of power in directive speaking action on Indonesia Lawyer Club Talk Show TV One. Method used in this research is descriptive qualitative. Data of this research was directive speaking action of moderator and interviewees on Indonesia Lawyer Club which include representation of power. Data were collected through open securitize speaking involvement with basic technique of take a note. Data were analyzed through several stages such as: data reduction, data presentation, and conclusion. The result of this research reveals 1) speech of moderator and on Indonesia Lawyer Club Talk Show TV One shows the existence of representation of power in directive speaking action in form of giving order, forbidding, giving advice, questions, inviting, requesting, and stating, 2) speech of moderator and on Indonesia Lawyer Club Talk Show TV One shows the existence of representation of function power in directive speaking action in form of giving order, forbidding, giving advice, questions, inviting, requesting, and stating. Power used by the moderator and speaker are legitimate power, coercive power, reward power, and expert power.